Investigation of the input signal frequency effect on the formed pulse of the hydraulic-powered pulse machine; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Novoseltseva M. V. Maria Viktorovna (Numerical Simulation of Applied Problems, 2016)
Title screen